The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3847/1538-4357/ab7455
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of γ-Ray Variability in Blazars

Abstract: We present an in-depth and systematic analysis of a sample of 20 powerful blazars, including 12 BL Lacs and 8 flat spectrum radio quasars, utilizing Fermi/LAT observations from the period 2008-2018 using various analysis tools such as flux distribution, symmetry analysis, and time series analysis. Results show that blazars with steeper γ-ray spectral indexes are found to be more variable; and the γ-ray flux distribution closely resemble both normal and lognormal probability distribution functions. The statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 101 publications
8
78
1
Order By: Relevance
“…Blazars are usually variable in practically all accessible bands, on diverse timescales and amplitudes. The general nature of the variability appears to be aperiodic, with the exception of a few sources such as Mrk 501, Mrk 421, S5 0716+714, PKS 1424 which are reported to show quasiperiodic oscillations [3,5]. The source in general are far away in the sense that the the telescopes with current capability hardly can resolve the central engine.…”
Section: Pos(icrc2021)606mentioning
confidence: 99%
See 2 more Smart Citations
“…Blazars are usually variable in practically all accessible bands, on diverse timescales and amplitudes. The general nature of the variability appears to be aperiodic, with the exception of a few sources such as Mrk 501, Mrk 421, S5 0716+714, PKS 1424 which are reported to show quasiperiodic oscillations [3,5]. The source in general are far away in the sense that the the telescopes with current capability hardly can resolve the central engine.…”
Section: Pos(icrc2021)606mentioning
confidence: 99%
“…In this proceeding, I present some of highlight of the works on -ray variability study of a sample of 20 blazar using the decade-long observation from Fermi/LAT telescope (see [3,4]. Section 2, the analysis methods are discussed and in Section 3 result and discussion are presented.…”
Section: Pos(icrc2021)606mentioning
confidence: 99%
See 1 more Smart Citation
“…The typical approach to search for periodicity at -ray energies in blazars is to analyze a limited sample of a few blazars and apply two or three time-series algorithms [e.g., 3,21]. In [10], we developed a pipeline to perform a search for periodicities in hundreds of blazars.…”
Section: < 50% Upper-limitsmentioning
confidence: 99%
“…Using the spectral analysis RobPer, Benitez et al [8] also found a periodicity of 310 d in optical, gamma, and X-ray data, also supporting the BBH hypothesis. [9] found a 280 d period in FERMI data, and Nilsson et al [11] found a period of 477 d in optical data. Contrary to these findings, Sandrinelli et al [7] analyzed gamma ray and optical light curves and found no significant periodicity in either.…”
Section: Introdunctionmentioning
confidence: 96%